Africa Development Indicators 2006 : From the World Bank Africa Database - World Bank (Africa Development Indicators, 2006)
Africa Development Indicators 2006 provides the most detailed collection of data on Africa available in one volume. It contains about 450 macroeconomic, sectoral, and social indicators, covering 53 African countries. Designed to provide all those interested in Africa with a focused and convenient set of data to monitor development programs and aid flows in the region, this is an invaluable reference tool for analysts and policymakers who want a better understanding of the economic and social developments occurring in Africa